Activation of spleen tyrosine kinase (SYK) contributes to neuronal pyroptosis and cognitive impairment in diabetic mice via the NLRP3/Caspase-1/GSDMD signaling pathway - Chenglong Zhou; Jun Li; Xiaochu Wu; Fei Liu (Experimental Gerontology, 2024)
Background/aim: Diabetes mellitus (DM) patients are at increased risk of cognitive impairment. The precise mechanisms underlying the association between DM and cognitive impairment remain unclear. Spleen tyrosine kinase (SYK), a crucial regulator of signal transduction, has been implicated in microglial pyroptosis in experimental ischemic stroke models. The present study investigated the potential role of SYK in DM-associated cognitive impairment. Methods: Diabetes was induced by streptozotocin (STZ) in C57BL/6 mice, and cognitive function and cerebral injury were assessed 12 weeks later using the Morris water maze (MWM), TUNEL assay and Western blotting. In vitro, the inhibition of SYK was investigated in a mouse hippocampal neuronal cell line cultured with high glucose. Results: Compared with control mice, DM mice presented impaired spatial learning and memory. Additionally, SYK activation was linked to neuronal pyroptosis, as evidenced by increases in the number of TUNEL-positive cells and protein levels of NLRP3, ASC, procaspase-1, caspase-1, GSDMD, the GSDMD N-terminal fragment, pro-IL-1β, and IL-1β in the hippocampus of DM mice. Compared with no treatment, SYK knockdown markedly attenuated cognitive impairment and histologic and ultrastructural pathological changes in the hippocampus of DM mice. The increased expression of pyroptosis-associated proteins and the increased number of TUNEL-positive cells were also significantly reduced. In vitro, high glucose significantly activated SYK to trigger the canonical pyroptotic pathway in cultured HT22 cells. The inhibition of SYK with a small interfering RNA or specific inhibitor significantly ameliorated the neuronal pyroptosis mediated by high glucose. Conclusion: Our findings demonstrate that SYK activation plays a pivotal role in promoting the cognitive impairment associated with DM. This effect is mediated by triggering neuronal pyroptosis through the canonical NLRP3/Caspase-1/GSDMD pathway. These results suggest that SYK may serve as a potential target for preventing or mitigating cognitive impairment in patients with DM.